The politics of religion in early modern France - Bergin, Joseph, 1948- (Yale University Press, 2014)
"Rich in detail and broad in scope, this majestic book is the first to reveal the interaction of politics and religion in France during the crucial years of the long seventeenth century. Joseph Bergin begins with the Wars of Religion, which proved to be longer and more violent in France than elsewhere in Europe and left a legacy of unresolved tensions between church and state with serious repercussions for each. He then draws together a series of unresolved problems--both practical and ideological--that challenged French leaders thereafter, arriving at an original and comprehensive view of the close interrelations between the political and spiritual spheres of the time. The author considers the powerful religious dimension of French royal power even in the seventeenth century, the shift from reluctant toleration of a Protestant minority to increasing aversion, conflicts over the independence of the Catholic Church and the power of the pope over secular rulers, and a wealth of other interconnected topics"--